The Dutch language in Japan (1600-1900) : a cultural and sociolinguistic study of Dutch as a contact language in Tokugawa and Meiji Japan - Joby, Christopher (Brill's studies in language, cognition and culture, ISSN 1879-5412, 2021)
"In The Dutch Language in Japan (1600-1900) Christopher Joby offers the first book-length account of the knowledge and use of the Dutch language in Tokugawa and Meiji Japan. For most of this period, the Dutch were the only Europeans permitted to trade with Japan. Using the analytical tool of language process, this book explores the nature and consequences of contact between Dutch and Japanese and other language varieties. The processes analysed include language learning, contact and competition, code switching, translation, lexical, syntactic and graphic interference, and language shift. The picture that emerges is that the multifarious uses of Dutch, especially the translation of Dutch books, would have a profound effect on the language, society, culture and intellectual life of Japan"--
Keywords: 1600-luku; 1700-luku; 1800-luku; Dutch language : Japan : History; Dutch language : Influence on Japanese; Japanese language : Foreign elements : Dutch; Languages in contact : Japan : History; Language and culture : Japan; Civilization : Dutch influences; Dutch language; Language and culture; Languages in contact; hollannin kieli; historia; japanin kieli; kieli ja kielet; kielihistoria; kielikontaktit; Japani; Japan : Civilization : Dutch influences; Japan